2020
DOI: 10.1101/2020.04.26.20080101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High frequency of SARS-CoV-2 RNAemia and association with severe disease

Abstract: 24Background: Detection of SARS-CoV-2 RNA in the blood, also known as RNAemia, has been 25 reported, but its prognostic implications are not well understood. This study aimed to determine 26 the frequency of SARS-CoV-2 RNA in plasma and its association with the clinical severity of 27 Methods: An analytical cross-sectional study was performed in a single-center tertiary care 29 institution in northern California and included consecutive inpatients and outpatients with COVID-30 19 confirmed by detection of SAR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 16 publications
4
38
2
1
Order By: Relevance
“…In our study the viraemia's percentage showed significant differences (p≤0,001) in ICU patients respect patients admitted in the ward with the two rRT-PCR assays; supporting previous studies which indicate that presence of SARS-CoV-2 RNA in serum samples is more common in critical patients and could be considerated a prognostic indicator (15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
“…In our study the viraemia's percentage showed significant differences (p≤0,001) in ICU patients respect patients admitted in the ward with the two rRT-PCR assays; supporting previous studies which indicate that presence of SARS-CoV-2 RNA in serum samples is more common in critical patients and could be considerated a prognostic indicator (15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
“…Viral RNAemia is detected in up to a third of COVID-19 patients, most often in patients with severe disease ( 3 , 19 ). EDTA plasma was available from all inpatients for SARS-CoV-2 rRT-PCR testing.…”
Section: Resultsmentioning
confidence: 99%
“…A recent proteomics study discovered strong association between the level of DC-SIGN and variants in the ABO locus, the glycosyltransferases required for blood group synthesis, a known genetic risk factor for respiratory failure in COVID-19 41 . Given that SARS-CoV-2 RNAemia is detected, particularly in patients with severe disease 38 , 42 , it is tempting to speculate that subsequent to CLR-dependent internalization, SARS-CoV-2 could be conveyed by CLR-expressing innate immune cells, and redistributed to permissive tissues where more damage could occur 43 . In accord with this hypothesis, a recent study revealed that SARS-CoV-2 nucleocapsid can be detected in spleens and lymph nodes 44 .…”
Section: Discussionmentioning
confidence: 99%